CXCR4‐SF1 bifunctional adipose‐derived stem cells benefit for the treatment of Leydig cell dysfunction‐related diseases. Issue 8 (17th March 2020) - Li, Xue; Xu, Ao; Li, Kai; Zhang, Jie; Li, Qin; Zhao, Gang; Zhang, Yue; Yuan, Hang; Guo, Yafei; Lin, Ping; Huang, Lugang
Abstract: Stem cell transplantation is a candidate method for the treatment of Leydig cell dysfunction‐related diseases. However, there are still many problems that limit its clinical application. Here, we report the establishment of CXCR4‐SF1 bifunctional adipose‐derived stem cells (CXCR4‐SF1‐ADSCs) and their reparative effect on Leydig cell dysfunction. CD29 + CD44 + CD34 − CD45 − ADSCs were isolated from adipose tissue and purified by fluorescence‐activated cell sorting (FACS). Infection with lentiviruses carrying the CXCR4 and SF1 genes was applied to construct CXCR4‐SF1‐ADSCs. The CXCR4‐SF1‐ADSCs exhibited enhanced migration and had the ability to differentiate into Leydig‐like cells in vitro. Furthermore, the bifunctional ADSCs were injected into BPA‐mediated Leydig cell damage model mice via the tail vein. We found that the CXCR4‐SF1‐ADSCs were capable of homing to the injured testes, differentiating into Leydig‐like cells and repairing the deficiency in reproductive function caused by Leydig cell dysfunction. Moreover, we investigated the mechanism underlying SF1‐mediated differentiation and testosterone synthesis in Leydig cells, and the B‐box and SPRY Domain Containing Protein (BSPRY) gene was proposed to be involved in this process. This study provides insight into the treatment of Leydig cell dysfunction‐related diseases.